Anatomical variations of sinonasal region: a CT scan study - Thimmappa, T. D.; Amith, P.; Nagaraj, M.; Harsha, K. N.; Gangadhar, K. S.; Azeem, Abdul (International Journal of Research in Medical Sciences, 2017)
Multislice CT is currently the imaging modality of choice for evaluating PNS & adjacent structures. Such a method has been increasingly utilized in the assessment of anatomical variations, allowing their accurate identification with high anatomical details. Some anatomical variations may predispose to sinonasal disease, constituting areas of high risk for injuries & complications during surgical procedures. Therefore, the recognition of such variations is critical in the preoperative evaluation for endoscopic surgery.